ANALISIS STUDI KELAYAKAN USAHA PRODUK SAMOSA CHICKEN HORTIKULTURA CURRY KHAS MALANG - Trivoni Giur, Gudelia; Suhendri, Hendrik; Indah, Sri (Unitri Press, 2025)
The business field that is currently popular in the community, especially in Malang, is the culinary field. The purchasing power of the people in Malang is quite high, because many people like to gather so that cafes and restaurants can be used as recommendations for comfortable places to be used as a gathering place with family and friends. To find out the parameters of Feasibility of Business Products Samosa Chiken Hortikultura Curry Khas Malang City and implement the results of the feasibility of Feasibility of Business Products Samosa Chiken Hortikultura Curry Khas Malang running well. In this study, researchers used a quantitative approach referring to a research approach based on positivistic understanding this research was conducted at Tribhuwana Tunggadewi University Malang (studio garuda). Data analysis techniques by detailing Investment Costs and Raw Material Requirements, How to Determine the HPP of Samosa Products, how to see the mark up value, how to determine BEP, profit / loss calculations, see the flow of cash flow must be positive, NPV calculation, IRR calculation, Payback Period. Based on the analysis of business feasibility by detailing investment costs and raw material requirements, it is known that it is Rp.70,006,310, HPP of Rp.7,958, Mark Up value of 0.45 (45%), BEP value per unit of Rp. 8,230 (pack / year) and for BEP price of Rp. 94,649,139, R / C of 1.45, positive cash flow of Rp.140,306,362, NPV calculation of Rp. 461,754,801, IRR calculation of 46%, Payback period.